Simplify:
1. 5 (-6) + (12 = 4))
3. (-6) - {(-28)= (-7)}
5. 11 - [(-8) - {10 - (9-7- 4)]
7. 10 - [8 - {11 + 30 = (4 - 5 - 71
Answers
Answered by
2
10-[8-{11+30÷(4–5–7)}]
=10-[8-{11-(30÷8)}]
=10-[8-(58÷8)]
=10-[6÷8]
=(80–6)÷8
=74÷8
=37÷4
=9.25 (Answer)
Attachments:
![](https://hi-static.z-dn.net/files/ddc/a74d45ea2d092caffedfb4219b6c7909.jpg)
![](https://hi-static.z-dn.net/files/d7f/61871d2dfd309f5f0c9593593e51f2ef.jpg)
![](https://hi-static.z-dn.net/files/dc0/2dac199f5861f0af48b093e814815ddc.jpg)
Answered by
0
Answer:
dcmbgmhckhcljfhlfhlfulfhlchchkckhcluhcgnxgmcjlcnfflgfnzykhkIyhysouosojsjh
Similar questions